DEVELOPING SCHOOLOGY-BASED E-LEARNING IN THE DOKKAI CHUKYU LEARNING COURSE - Kadek Eva Krishna Adnyani; Desak Made Sri Mardani; Ni Nyoman Murniasih; I Wayan Adnyana (Jurnal Nasional Pendidikan Teknik Informatika : JANAPATI, 2020)
This research aims to know: (1) what form of schoology appropriate for the dokkai chukyu learning course in Japanese language education department UNDIKSHA is, and (2) how the quality of schoology for the dokkai chukyu learning course in Japanese language education department UNDIKSHA is? This is Research and Development (R&D) using the development model of ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The data collection methods were observation and questionnaire while the instruments used were in the forms of questionnaire and observation sheets. Assessment of the quality of the product was performed by one expert in material, one expert of learning media, and 10 learners of the dokkai chukyu language course in Japanese language education department. Based on the assessment results of experts of material and media, schoology was determined as very good and could be used with revision. Stages of the evaluation were conducted using questionnaires to fill out by 10 students of the dokkai chukyu course. The student response on schoology was predominately positive, i.e. agree and strongly agree.